Developing Augmented Reality (AR) as Assisted Technology in Reading Based on Content-Language Integrated Learning - Yulian, Ryani; Ruhama', Ufi; Sucipto (JTP - Jurnal Teknologi Pendidikan, 2022)
Assisted technology has become one of the primary needs for inclusive education, especially for language learning. Language learning mediated by technology can provide affordances to EFL learners with low English language skills. Therefore, an assisted technology with content-language integrated learning was developed with the ADDIE approach to producing meaningful and motivational language learning with a dual focus, namely content and language. The materials presented in the assisted technology were developed stick to the Line-of-Sight by the Branch model (2009), which covers needs, goals, strategies, and assessment. The technology and material development result were named assisted technology-enhanced language learning (ATELL) and created with a marker-based augmented reality application. The AR application is an assisted technology for reading comprehension skills that guide the students in critical thinking for critical reading activities. The findings of the study show that students who read with the AR application performed better than those who read with the traditional method. The students also reported that they have a positive perception of the integration of the AR application for language learning for several attributes such as technology interactivity, compatibility, learning ambience, and cognitive condition.